Penguatan Literasi Digital melalui Pembelajaran Koding di Sekolah Dasar untuk Melatih Computational Thinking - Hikmatunisa, Nenden Permas; Mutmainah, Nadia Tiara Antik Sari, Elsa; Insari, Farah Rosmelia, Indah Putri; Jabalrohmah, Lidya Damayanti, Nisa; Meilandani, Putri Anandika Pratiwi, Risfi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Abstract Computational thinking is the ability to break down problems, recognize patterns, abstract, and systematically construct solutions. This research aims to develop students' digital literacy skills thru coding lessons that are presented in a fun, contextual, and age-appropriate manner, using a participatory action research (PAR) approach. The results of this study indicate that Scratch-based coding training can develop digital literacy skills and train computational thinking. However, in practice, there are still obstacles such as differences in basic digital literacy skills, a lack of infrastructure, and less competent educators. Therefore, Scratch-based coding learning can be an effective solution for developing digital literacy skills and training computational thinking.